Herpes Simplex Virus Infection in Pregnancy - Gianluca Straface; Alessia Selmin; Vincenzo Zanardo; Marco De Santis; Alfredo Ercoli; Giovanni Scambia (Hindawi Limited, 2012)
Infection with herpes simplex is one of the most common sexually transmitted infections. Because the infection is common in women of reproductive age it can be contracted and transmitted to the fetus during pregnancy and the newborn. Herpes simplex virus is an important cause of neonatal infection, which can lead to death or long-term disabilities. Rarely in the uterus, it occurs frequently during the transmission delivery. The greatest risk of transmission to the fetus and the newborn occurs in case of an initial maternal infection contracted in the second half of pregnancy. The risk of transmission of maternal-fetal-neonatal herpes simplex can be decreased by performing a treatment with antiviral drugs or resorting to a caesarean section in some specific cases. The purpose of this paper is to provide recommendations on management of herpes simplex infections in pregnancy and strategies to prevent transmission from mother to fetus.